EFFECT OF AUTHENTICAL ASSESSMENT AND HIGH ORDER THINKING SKILL (HOTS) AGAINST TROUBLESHOOTING PHYSICAL PROBLEMS (An Experiment in The Students of SMA Negeri 2 Depok City) - Eni Widyastuti (Jurnal Evaluasi Pendidikan, 2017)
This research aims to see the effect of authenticity and high order thinking skill (HOTS) on the problem solving of physics. Authentic assessment forms include performance and portfolio. High order thinking skill (HOTS) includes high order thinking skill (HOTS) high and high order thinking skill (HOTS) low. The method of research uses an experimental method. While the design of research uses treatment by level 2 x 2. The hypotheses of research were tested using two way of analysis of variance (ANAVA). The result of research concluded that: (1) the results of students 'group physics problem solving abilities that were given an authentic form of higher-performing performance than the students' group physics problem solving abilities that were given an authentic portfolio assessment form; (2) there was a significant interaction effect between the authentic form of assessment and high order thinking skill (HOTS) to the results of physics problem solving ability; (3) special group of students who have high order thinking skill (HOTS) high, the result of problem solving ability of physics group of students who are given form of authentic assessment of performance is higher than the result of problem solving problem of physics group of students; (4) special group of students who have high order thinking skill (HOTS) is low, the result of problem solving ability of physics group of students who are given the form of authentic assessment of performance is lower than the result of the problem solving ability of the physics group of students who are given the form assessment a portfolio utilities.